Relation of Serum Leptin with sex Hormones of obese Infertile Men and Women - Reshma Farooq, Sualiha Lutf Ullah & Humera Ishaq (Journal of Applied Pharmaceutical Science, 2013)
The present study was designed to evaluate the relationship between serum leptin and sex hormones in obese infertile men and women. Sex hormones (LH, FSH and testosterone) and serum leptin of infertile obese men (n=66) and women (n=30) compared with control fertile men (n=60) and women (n=30) with same ages to find the relation and contribution of serum leptin and sex hormones in causation of fertility or infertility. The results revealed that Serum leptin level in obese (BMI>240 fertile and infertile male and female were significantly (p
Keywords: Serum leptin, Sex hormones, Obese infertile, Men and women.